Pengaruh Naungan Terhadap Pertumbuhan Bibit Aquilaria malaccensis Lam. Di Persemaian BPDASHL Tondano Kima Atas Manado - Sahrin Lingga; Marthen. Th. Lasut; Euis F. S. Pangemanan (Universitas Sam Ratulangi, 2022)
Abstract Aquilaria malaccensis Lam. is a type of tree belonging to the agarwood tribe (Thymelaeaceae) which can be found in Bangladesh, Bhutan, India, Indonesia, Iran, Laos, Malaysia, Myanmar, Philippines, Singapore, and Thailand (Kamonwannasit, 2013). This study aims to determine the effect of shade on the growth of A, malaccsens seedlings. The treatment with shade had an effect on without shade (P1) 33.12 cm giving the highest average height increase since the beginning of the observation, while the treatment with shade P4 (90%) was 26.38 cm and the smallest shade treatment was P3 (90%) 25.86 cm (week II to week II). XIII) compared with other treatments.). stem diameter of seedlings of A. malaccensis in the treatment without shade P1 0.34 mm had the highest value compared to other treatments, while the treatment with shade P3 2 (75%) 0.2 mm and the smallest shade treatment P4 (90%) 0.16 mm during the observation period (week II – week XII). The increase in the number of leaves to the shade treatment was the highest P3 (75%) 17.2 leaves without shade P1 17.2 leaves while the lowest shade treatment was P4 (90%) to the increase in the number of leaves during the observation period (week II – week XIII). Keywords: Aquilaria malaccensis Lam., Effect of shade, Growth